Toxoplasma gondii in women of childbearing age and during pregnancy: seroprevalence study in Central and Southern Italy from 2013 to 2017 - Fanigliulo, Daniela (Parasite, 2020)
Toxoplasmosis is a worldwide health problem. Infection in pregnant women can result in severe fetal morbidity or in subclinical neonatal infection; most subclinical cases develop ocular and neurological sequelae. The purpose of this serological study was to assess the prevalence of Toxoplasma gondii in two populations of women of childbearing age in Siena (Tuscany, Central Italy) and Bari (Apulia, Southern Italy) between 2013 and 2017 and in a group of pregnant women in Bari in 2016–2017. Serum samples were tested for the presence of specific anti-Toxoplasma gondii IgG antibodies by a commercially available ELISA test. The percentage of seropositive subjects in Bari was significantly higher than in Siena (22.4% vs. 12.4%) and an age-related trend was observed. A low prevalence of T. gondii infection (13.8%) was observed among the pregnant women tested. In addition to showing a significant difference between Central and Southern Italy, this study provides updated data on T. gondii seroprevalence in women during childbearing age and pregnancy. The results confirm a trend toward a decrease, especially in younger people and pregnant women.